AYURVEDIC APPROACH IN ORAL HEALTH & HYGIENE: A REVIEW - Garg, *Gunjan; Mangal, Gopesh; Chundawat, N.S. (International Journal of Ayurveda and Pharma Research, 2016)
Oral diseases continue to be a major health problem world-wide with the incidence of oral cancer and other disorders are on the rise in developing countries. Oral health also reflects the body health. For prevention and the treatment of oral diseases, modern medicine has had only limited success. There is a global need for safe and effective alternative prevention and treatment. Ayurveda is good alternative for that and may lead to the development of novel preventive or therapeutic strategies for oral health. This 5000-year-old system of medicine not only recommends treatments with specific herbs and minerals to cure various oral diseases but also recommends some daily use therapeutic procedures for the prevention of and maintenance of oral health. Recently, there is renewed interest in use of Ayurvedic drugs for oral health. Various Ayurvedic herbs and natural products have been used for their pharmacological applications viz. antiulcer, wound healing, anti-inflammatory, antimicrobial and antioxidant properties and have been proven to be safe and effective for oral disease and hygiene including various therapeutic Ayurvedic procedures. Scientific validations of the Ayurveda oral health practices could justify their incorporation into modern oral care. In this paper, an attempt has been made to scientific evidence based review various therapeutic procedures for the prevention and maintenance of oral health and hygiene mentioned in Ayurveda.